2007
DOI: 10.4049/jimmunol.179.6.3452
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cells Biased for IL-5 Production Act as Crucial Regulators of Inflammation

Abstract: Although invariant NKT (iNKT) cells play a regulatory role in the pathogenesis of autoimmune diseases and allergy, an initial trigger for their regulatory responses remains elusive. In this study, we report that a proportion of human CD4+ iNKT cell clones produce enormous amounts of IL-5 and IL-13 when cocultured with CD1d+ APC in the presence of IL-2. Such IL-5 bias was never observed when we stimulated the same clones with α-galactosylceramide or anti-CD3 Ab. Suboptimal TCR stimulation by plate-bound anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 45 publications
(53 reference statements)
1
55
0
1
Order By: Relevance
“…49,50 A fraction of human NKT has also been shown to secrete high amounts of IL-5 and IL-13. 18,50,51 Therefore, secretion of these two cytokines by DP TAL suggest that these cells might play, at the effector level, roles similar to those of NKT. Nonetheless, DP and NKT likely have different ligands because DP do not express the NKT invariant TCR Va24 and in addition lack CD56.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 A fraction of human NKT has also been shown to secrete high amounts of IL-5 and IL-13. 18,50,51 Therefore, secretion of these two cytokines by DP TAL suggest that these cells might play, at the effector level, roles similar to those of NKT. Nonetheless, DP and NKT likely have different ligands because DP do not express the NKT invariant TCR Va24 and in addition lack CD56.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies revealed that while this robust IL-4 production was a signature of iNKT cells, it certainly was not the only cytokine iNKT cells can produce. To date, iNKT cells have been shown to produce IFN-γ and IL-4, as well as IL-2, IL-5, IL-6, IL-10, IL-13, IL-17, IL-21, TNF-α, TGF-β and GM-CSF ( Figure 1A) [21][22][23][24][25][26]. iNKT cells are also known to produce a vast array of chemokines [27].…”
Section: Cytokine and Chemokine Productionmentioning
confidence: 99%
“…Allergic diseases, including asthma, are characterized by inflammation with pronounced infiltration of eosinophils and CD4+ T cells. IL-5 is a cytokine that is highly specific for eosinophilic inflammation and was originally found as 'T-cell replacing factor' that is secreted from T cells to stimulate antibody production from activated B cells [16]. IL-5 seems to be the primary cytokine involved in vivo in the production, differentiation, maturation and activation of eosinophils [9].…”
Section: Discussionmentioning
confidence: 99%